The role of immunocytochemical biomarkers in diagnostics of precancerous pathology of cervix - I.Z. Gladchuk; N.M. Rozhkovska; N.M. Kashtalian (Medičnì Perspektivi, 2021)
The last decades showed the worldwide tendency to finding consensus between diagnostics improvement and constant increase of cost of medical services in conditions of restricted financing. The aim of the article was to analyze the diagnostic value of p16 and Ki-67 biomarkers in diagnostics of precancerous diseases of cervix. Data of 80 patients with cervical dysplasia of varying degree who received excisional treatment were analyzed. It was shown that cytological study has a high sensitivity (79.17%) for the diagnosis of CIN 2-3, but low specificity (53.57%). The p16 immunocytochemical biomarker has a high sensitivity for the diagnosis of CIN 2 (0.92; 95% CI: 0.76-0.98) with good specificity (0.78; 95% CI: 0.67-0.82), for the diagnosis of CIN 3 both sensitivity (0.93; 95% CI: 0.82-0.98) and specificity (0.93; 95% CI: 0.82-0.98) is high. The immunocytochemical biomarker Ki-67 has a high sensitivity for CIN 2 (0.92; 95% CI: 0.65-0.99), but insufficient specificity (0.62; 95% CI: 0.54-0.64), for the diagnosis of CIN 3 the sensitivity is very high (0.96; 95% CI: 0.80-0.99) as well as specificity (0.78; 95% CI: 0.69-0.81). The combined use of p16 and Ki-67 biomarkers can significantly increase the diagnostic accuracy of the diagnosis of high-grade precancerous pathology of cervix and justify timely surgical intervention. Such an approach for the differential diagnosis of severe dysplasia, on the one hand, may contribute to a decrease in the risk of developing cervical cancer, and on the other hand, it will allow to avoid unnecessary operations and preserve reproductive function of women, reduce the economic costs of treatment.